Be prepared: online school experience and student achievement during the pandemic - Beck, Dennis (Frontiers in Education, 2023)
During the COVID-19 pandemic it was clear that not all schools were equally prepared to adapt to the challenges of online learning. While many traditional public schools struggled to transition to remote teaching, cyber charter schools–which already had experience with full-time online learning–appeared to demonstrate superior academic performance and less learning loss. This success may be due in part to the greater experience of these schools with online teaching, as well as that the type of student enrolling in cyber charters changed. Further research and external peer review is necessary to confirm the validity of these findings, but in the face of uncertainty and change, it is essential that we approach education with an open mind and a willingness to consider all perspectives in order to find solutions that truly benefit our students.